2020
DOI: 10.1016/j.ejro.2020.100277
|View full text |Cite
|
Sign up to set email alerts
|

Imaging differences between coronavirus disease 2019, severe acute respiratory syndrome, and Middle East respiratory syndrome

Abstract: Since the outbreak of Coronavirus Disease-19 (COVID-19) infection in December 2019 in Wuhan, the capital Hubei province, central of China, more than 4 million people have contracted the virus worldwide. Despite the imposed precautions, coronavirus disease-19 is rapidly spreading with human-to-human transmission resulting in more than 290,000 death as of May 13, 2020 according to World Health Organization (WHO). The aim of this study was to revise the characteristic imaging features of Sever Acute Respiratory S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…After analyzing our results, with the experience gained in the first two COVID-19 waves and based on the existing literature review we have performed a local protocol listing specific and age-adjusted indications for the performance of chest X-ray among pediatric patients with confirmed or suspected COVID. We prioritized in the indications the presence of symptoms and symptoms duration, specially fever, as it has already been published how chest X-ray sensitivity increases after 5 days of symptoms [34,35]. We also include specific indications for children with suspected MIS-C and for infants as they are known to present worst clinical evolutions [10].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After analyzing our results, with the experience gained in the first two COVID-19 waves and based on the existing literature review we have performed a local protocol listing specific and age-adjusted indications for the performance of chest X-ray among pediatric patients with confirmed or suspected COVID. We prioritized in the indications the presence of symptoms and symptoms duration, specially fever, as it has already been published how chest X-ray sensitivity increases after 5 days of symptoms [34,35]. We also include specific indications for children with suspected MIS-C and for infants as they are known to present worst clinical evolutions [10].…”
Section: Resultsmentioning
confidence: 99%
“…From 5506 children with confirmed COVID-19 in Navarre, only 44 were admitted into hospital, and only 35 had a chest radiograph performed (6 % of all SARS-CoV-2 pediatric cases and 80 % of hospitalized children). In our review, chest radiograph was the most common imaging technique used to diagnose pneumonia or respiratory tract infection in children and, while in adults CT is very commonly used, only one pediatric patient required a chest CT [34]. Even though chest X-ray remains the principal technique imaging recommended, lung ultrasound, is a non-invasive, easily repeatable useful diagnosing tool.…”
Section: Discussionmentioning
confidence: 99%
“…In other corona virus infection, a similar initial pattern of ground-glass opacities and consolidation and late reticular patterns were observed a 30 cases analysis severe acute respiratory syndrome (SARS), though pleural effusion was not a documented feature [ 20 ]. It was concluded that bilateral lung involvement on initial imaging is more likely to be seen with COVID-19, while unilateral lung involvement is more likely to be seen in SARS and MERS [ 21 ].…”
Section: Discussionmentioning
confidence: 99%